Ethnoecological Study of Sendang Surodilogo in Kertek District, Wonosobo Regency as a Learning Resource - Saputro, Frengki; Siti Alimah (Universitas Negeri Semarang, 2025)
This study investigated the ethnoecological characteristics of Sendang Surodilogo, a culturally and ecologically significant spring located in Pagerejo Village, Kertek District, Wonosobo Regency, and developed a profile book as a contextual learning resource for biology education. Using a modified Borg and Gall Research and Development model, the research involved preliminary exploration, field data collection, product design, expert validation, revision, and small-scale field testing. A descriptive exploratory approach was used to document cultural narratives, ecological perceptions, and vegetation diversity around the spring. Data were collected from formal participants (biology teacher and students) and nonformal participants representing three age groups (30, 40, and 50 years old) using interviews, questionnaires, and documentation. The findings revealed that the community possesses strong ethnoecological knowledge reflected through myths, rituals, and conservation practices linked to the symbolic figure of Ki Joko Suro. Vegetation analysis recorded species belonging to Spermatophyta, Pteridophyta, and Bryophyta, each contributing to hydrological stability and microhabitat formation. Expert validation rated the material at 93.61% and media at 91.36%, placing the product in the “very feasible” category. Field testing also resulted in positive responses, with formal participants scoring 85.7% and nonformal participants 85.3%. Overall, Sendang Surodilogo holds substantial ecological and cultural value. Its documentation into a profile book demonstrates strong potential as a contextual biology learning resource, enriching environmental literacy and promoting culture-based science education